DECISION SUPPORT SYSTEM IN GIVING BEST EMPLOYEE REWARD USING AHP (ANALYTICAL HIERARCHY PROCESS) METHOD CASE STUDY PT. SWASTIKA ANUGRAH PACK - Khairul Anwar; Muhammad Syahputra Novelan; Zulfahmi Syahputra (Sean Institute, 2022)
In improving the performance of employees at the company PT. The Anugrah Swastika package is by giving rewards to employees so that their morale continues to increase and they are given awards for being the best employees. One way to implement or implement it is to create a decision support system in giving awards to the best employees by making several criteria that will be considered. In this study, the method that will be applied is AHP (Analytical Hierarchy Process) by giving weighting to each criterion that will be assessed by each person. The criteria that will be assessed are quality of work, quantity of work, speed of work, mastery of fields, discipline, initiative and loyalty.